权力与情感 ：武后故事的现代改编以电视剧《武媚娘传奇》为研究中心 = Power and emotion : modern adaptation of the stories of Empress Wu : a research on serial TV drama “The Empress of China” - 于丹宁 Yu, Danning (2015)
武后是一个传奇式人物，她的故事自古至今流传于民间。从史籍到文学，武后形象在不断演变。本文整理了武后故事的不同体裁，以诗歌、小说、戏曲和现代影视为主，从中揭示武后丰富的艺术形象。权力自然是围绕武后故事的一个焦点话题， 但是，本文认为这位女皇一生的爱情和亲情更是值得人们去发掘的，因此，本文以现代电视剧《武媚娘传奇》为中心重新诠释武后权力和情感之间的关系，包括她的爱情和亲情。最后，本文探讨不同年代具有代表性的武后故事影视作品的改编差异， 并从社会各界对《武媚娘传奇》改编的反响程度，试图探究其作为电视媒体所应持有的改编限度。Empress Wu is a legendary figure and her story has been a popular folklore from ancient China until now. From historical records to literature writing, Empress Wu’s image is undergoing constant change. This paper shows her rich feature artistic characters through analyzing the different literature genres in which her story has been displayed, including poetry, novels, dramas and modern serial dramas. Power is a key factor in the story of Empress Wu, but her love and kinship even make up the soul of the story; hence, this paper discusses how the serial drama “The Empress of China” portrays the relationship between Empress Wu’s power and emotion. Lastly, this paper compares the difference of adaptation among representative serial dramas of Empress Wu’s story in different generations and explores the limitations of adaptation in serial drama “The Empress of China” as TV Media.